2022
DOI: 10.3389/fphys.2022.833809
|View full text |Cite
|
Sign up to set email alerts
|

Low-Intensity Resistance Exercise Combined With Blood Flow Restriction is More Conducive to Regulate Blood Pressure and Autonomic Nervous System in Hypertension Patients—Compared With High-Intensity and Low-Intensity Resistance Exercise

Abstract: Background: The effect of resistance exercise on the autonomic nervous system of patients with hypertension has not been identified.Objective: To explore a suitable resistance training method for hypertension patients to regulate blood pressure (BP) and autonomic nervous system function.Method: Forty-five hypertension patients aged between 55 and 70 years were randomly equally divided into three groups: the high-intensity resistance exercise (HE) group, the low-intensity resistance exercise combined with blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…The results of this work shows the need for further studies, with combinations of methods, such as western blot, for the identification and confirmation of proteins seen here in salivary proteomics and with a high number of participants, as well as it would be interesting to verify the long‐term protein profile of BFR protocol, as well as its comparison in hypertensive individuals, since the literature has shown benefits of BFR in these individuals, 49 and comparison to HI protocol in trained individuals and those with the aforementioned diseases, to see the potential benefits of practicing this protocol.…”
Section: Discussionmentioning
confidence: 88%
“…The results of this work shows the need for further studies, with combinations of methods, such as western blot, for the identification and confirmation of proteins seen here in salivary proteomics and with a high number of participants, as well as it would be interesting to verify the long‐term protein profile of BFR protocol, as well as its comparison in hypertensive individuals, since the literature has shown benefits of BFR in these individuals, 49 and comparison to HI protocol in trained individuals and those with the aforementioned diseases, to see the potential benefits of practicing this protocol.…”
Section: Discussionmentioning
confidence: 88%
“…While, by the findings of Junior et al (2019) , our results showed that the time domain indicators of HRV, SDNN and RMSSD, were significantly elevated in BFRT group, and the reason for this discrepancy could be attributed to the different forms and amount of exercise, and the subject variance. LF closely represents sympathetic regulation, and HF is an indicator of vagal regulation ( Zhao et al, 2022 ). In the present study, HF and LF were also found to be significantly elevated in BFRT group, with enhanced sympathetic and parasympathetic excitability, possessing improved regulation relative to resistance training alone.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term cardiorespiratory endurance training is characterized by low intensity, long duration, and high rhythm, which may be effective in controlling hypertension [ 14 ]. Studies have shown that resistance training lowers blood pressure as much or more than aerobic training [ 15 , 16 ]. However, resistance training involves more forceful movements and patients may experience reactions such as dizziness, nausea and stomach upset, so a pre-assessment of the participant’s physical condition is required [ 17 ].…”
Section: Introductionmentioning
confidence: 99%